2016
DOI: 10.1186/s12866-016-0770-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community characterization of water and intestine of the shrimp Litopenaeus stylirostris in a biofloc system

Abstract: BackgroundBiofloc technology (BFT), a rearing method with little or no water exchange, is gaining popularity in aquaculture. In the water column, such systems develop conglomerates of microbes, algae and protozoa, together with detritus and dead organic particles. The intensive microbial community presents in these systems can be used as a pond water quality treatment system, and the microbial protein can serve as a feed additive. The current problem with BFT is the difficulty of controlling its bacterial comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
163
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 40 publications
23
163
0
3
Order By: Relevance
“…; Cardona et al . ). Present investigations also revealed significant ( P < 0·05) increase in microbial flora of Firmicutes , where genus Lactobacillus was enriched in water after Bio‐ball treatment.…”
Section: Resultsmentioning
confidence: 97%
“…; Cardona et al . ). Present investigations also revealed significant ( P < 0·05) increase in microbial flora of Firmicutes , where genus Lactobacillus was enriched in water after Bio‐ball treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Water and sediment, which are important components of the culture environment, are closely related to the growth of shrimp (Cardona et al, ; Del'Duca, ; Wang et al, ). A previous study showed that microorganisms, bacterium and microalgae could accumulate, grow and multiply on the surface of BWPG and gradually form a complex biofilm structure (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two grams surface sediment samples were used to precipitate microorganisms via oscillation, incubation and centrifugation. After 24 hr of fasting, sixty healthy shrimps of same size, body colour and body surface were randomly collected from the two ponds and were divided into three groups randomly (Cardona et al, ). Shrimp intestine samples were then removed from the abdominal cavities with a sterile tweezer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations